Don't be silly, mr. twiddle! - Blyton, Enid (Award Publications Limited, 2010)
Don't Be Silly, Mr. Twiddle! by Enid Blyton is a whimsical children's book featuring the lovable but forgetful Mr. Twiddle, who often finds himself in comical predicaments due to his absent-mindedness. The story unfolds as Mr. Twiddle attempts to carry out simple tasks, only to be sidetracked by his own silly thoughts and ideas. His well-meaning intentions lead to a series of humorous misunderstandings with his friends and family. Through Mr. Twiddle$1 (Bs escapades, the book captures the charm of everyday life while teaching young readers about kindness and the importance of friendship, all wrapped in delightful, lighthearted storytelling.s